Digital media and self-learning: the role of the library - Ember, Kristina (Norma, 2022)
The paper is about a role of digital media in developing a new culture of learning and the possibilities of connecting education with libraries as places of universal knowledge that are increasingly accessible through the internet. The first part of the paper deals with the acknowledgement of traditional teaching beginning with guided learning, through major transformations in the education system, to the introduction of a new culture of learning where self-learning is promoted. The teacher appears to be a mentor while students are active participants in accessing information and acquiring new knowledge. They are getting used to lifelong learning by using digital media which have incentive role in encouraging independent learning. It is necessary to incorporate digital media in children`s education from the earliest age, and all the way through education, as well as in professional education of young people and in the education of older people to encourage self learning and life long learning. The second part reveals the role of libraries in information and media literacy of students, which is extremely important for self-learning. In earlier decades, literacy ment learning to read and write and involved comprehension of content while today literacy is using of contemporary media and skills to seek and select information. The role of library in developing a new literacy lies upon its transformation from traditional to information centar which offers e books, all kinds of information and also free points to use internet.